6
$\begingroup$

I know that it can be also evaluate using Taylor expansion, but I am intentionally want to solve it using L'Hôpital's rule:

$$ \lim\limits_{x\to 0} \frac{\sin x}{x}^{\frac{1}{1-\cos x}} = \lim\limits_{x\to 0}\exp\left( \frac{\ln(\frac{\sin x}{x})}{1-\cos x} \right)$$

Now, from continuity and L'hopital Rule: $$\lim\limits_{x\to 0} \frac{\ln(\frac{\sin x}{x})}{1-\cos x} = \lim\limits_{x\to 0} \frac{\frac{x}{\sin x}\cdot\frac{x\cos x - \sin x}{x^2}}{\sin x} = \lim\limits_{x\to 0}\frac{\frac{x\cos x - \sin x}{x\sin x}}{\sin x}$$

This is where I got stuck.
If I'm not mistaken the limit is $-\frac{1}{3}$ so the orginial one is $e^{-\frac{1}{3}}$

What should I do different (Or what's is wrong with my calculation?)
Thanks

$\endgroup$
  • $\begingroup$ Have you tried applying the rule again? $\endgroup$ – Najib Idrissi Aug 8 '14 at 15:40
6
$\begingroup$

After rearranging the quotient a bit we can apply L'hopitals rules $2$ more times to get the answer:

$$\lim_{x\to0}\frac{x\cos(x)-\sin(x)}{x\sin^{2}(x)}\underbrace{=}_{\text{l'hopital}}\lim_{x\to0}\frac{-x\sin(x)}{\sin^{2}(x)+2x\sin(x)\cos(x)}=\lim_{x\to0}\frac{-x}{\sin(x)+2x\cos(x)}$$

$$\underbrace{=}_{\text{l'hopital}}\lim_{x\to0}\frac{-1}{3\cos(x)-2x\sin(x)}=\frac{-1}{3}$$

$\endgroup$
  • $\begingroup$ Thanks, I should have just continue and not give up :) $\endgroup$ – Elimination Aug 8 '14 at 15:56
  • $\begingroup$ You're welcome. $\endgroup$ – user71352 Aug 8 '14 at 16:01
3
$\begingroup$

You can continue it as the following : $$\begin{align}\lim_{x\to 0}\frac{x\cos x-\sin x}{x\sin^2 x}&=\lim_{x\to 0}\frac{(x\cos x-\sin x)'}{(x\sin^2 x)'}\\&=\lim_{x\to 0}\frac{\color{red}{\cos x}-x\sin x\color{red}{-\cos x}}{\sin^2 x+2x\sin x\cos x}\\&=\lim_{x\to 0}\frac{-x}{\sin x+2x\cos x}\\&=\lim_{x\to 0}\frac{-1}{(\sin x/x)+2\cos x}\\&=\frac{-1}{1+2\cdot 1}.\end{align}$$

$\endgroup$
  • $\begingroup$ @Elimination: You are welcome. $\endgroup$ – mathlove Aug 8 '14 at 16:05
2
$\begingroup$

Alternative approach using Taylor series:

Using $\frac{\sin x}{x} = 1 - \frac{x^2}{6} + o(x^2)$ we get $\ln(\frac{\sin x}{x}) \sim_0 \ln(1-\frac{x^2}{6})$. This expression has the Taylor expansion $-\frac{x^2}{6}+o(x^2)$.

We can approximate the denominator by $1-\cos x=\frac{x^2}{2} + o(x^2)$.

Then we have: $\frac{\ln(\frac{\sin x}{x})}{1-\cos x} \sim_0 -\frac{x^2}{6} \frac{2}{x^2} = -\frac{1}{3}$.

This doesn't exactly answer your question, but hopefully it provides a little bit of insight. :)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.